Survei Indeks Kepuasan Masyarakat Pada Badan Penanggulangan Bencana Daerah Kabupaten Kutai Kartanegara Tahun 2018 - Heru Suprapto (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
Abstract : The Regional Disaster Management Agency (BPPD) has the main task of assisting the Regent in carrying out Government Affairs which is the authority of the Region and the Assistance Task for Regional Disaster Management. This task is very responsible for disaster management that occurred in Kutai Kartanegara Regency. Regarding this, evaluation of the implementation of duties and functions needs to be carried out regularly and continuously to maintain and improve the quality of services to the community. This survey activity is generally intended to determine the perception of public satisfaction with the service performance of the BPPD Kutai Kartanegara Regency. The sample in this study amounted to 120 samples spread over 5 (five) districts. The results showed that the Community Satisfaction Index in the regional disaster management agency of Kutai Kartanegara Regency based on the District. The score is declared Good based on Permen PAN & RB No.16/2014. Of the 8 Service Elements used in the IKM survey the average score was 2.805, the score was declared Good based on the PAN & RB Permen No. 16/2014. In the Complaint Handling Element, Suggestions and Inputs, for the communication media indicators for suggestions and input, a score of 1.028 was obtained or the service quality was not good based on the PAN & RB Regulation No. , Infrastructure improvement indicators Permenpan & RB No.14 / 2017 is also not good. In the product and public facilities element, a score of 2.056 was obtained, the quality of service was not good, based on Permenpan & RB No. 16/2014, while based on Permenpan & RB No.14 / 2017 it is not good. Keywords: Service Quality, Community Satisfaction, Disaster